Changes in Shared Decision-Making Roles and Perceived Stress in Syrian Refugee Parents Resettled in the Greater Toronto Area - Boulos, Maria; Hynie, Michaela; Spirling, Shauna; Tamim, Hala (Refuge: Canada's Journal on Refugees, 2024)
This study explored changes in shared decision-making roles (day-to-day, financial, and major life decisions) and their relationships to perceived stress among 148 Syrian refugee parents after resettling in Toronto using a generalized estimated equation model. Parents were categorized as “towards shared” decision-making for 20.3%, 23.0%, and 21.6% of day-to-day, major life, and financial decisions, respectively. In families where both parents were unemployed, those who “always shared” making financial decisions had significantly lower perceived stress than those “towards shared” (p = .02). Understanding the cultural contexts of gender roles and the impact of acculturation may help promote better post-migration strategies.